Decentralization and Redistribution Irrigation Reform in Pakistan's Indus Basin - Jacoby, Hanan G. (The World Bank, 2018)
Does decentralizing the allocation of public resources reduce rent-seeking and improve equity? This paper studies a governance reform in Pakistan's vast Indus Basin irrigation system. Using canal discharge measurements across all of Punjab province, the analysis finds that water theft increased on channels taken over by local farmer organizations compared with channels that remained bureaucratically managed, leading to substantial wealth redistribution. The increase in water theft was greater along channels with larger landowners situated upstream. These findings are consistent with a model in which decentralization accentuates the political power of local elites by shifting the arena in which water rights are contested